Incompatibility assessment of Genkwa Flos and Glycyrrhizae Radix et Rhizoma with biochemical, histopathological and metabonomic approach. (30th January 2019) - Chen, Yan-Yan; Tang, Yu-Ping; Shang, Er-Xin; Zhu, Zhen-Hua; Tao, Wei-Wei; Yu, Jin-Gao; Feng, Li-Mei; Yang, Jie; Wang, Jing; Su, Shu-Lan; Zhou, Huiping; Duan, Jin-Ao
Abstract: Ethnopharmacological relevance: As recorded in traditional Chinese medicine (TCM) theory, Genkwa Flos (YH) and Glycyrrhizae Radix et Rhizoma (GC) compose one herbal pair of the so-called "eighteen incompatible medicaments", which indicate pairs of herbs that are mutually incompatible and that theoretically should not be applied simultaneously. However, the theory has been called into question due to a lack of evidence. Aims of study: In this study, the incompatibility of YH and GC was investigated based on an assessment of the toxic effects of their combination by traditional safety methods and a modern metabonomic approach. Materials and methods: Sprague-Dawley rats were used to evaluate the subacute toxicity of YH and YH-GC. The serum, urine, and several tissues were collected for biochemical analysis, histopathological examination, and metabonomic analysis. Results: Rats exposed to a dose of 1.0 g/kg YH (3 times of the Chinese Pharmacopoeia maximum dose) exhibited toxicity of the heart, liver, kidney and testes, and rats exposed to a YH-GC combination (1.0 g/kg YH + 1.0 g/kg GC) exhibited similar hepatotoxicity, which aggravated renal and reproductive toxicity. Following this, a metabonomic study tentatively identified 14 potential biomarkers in the YH group and 10 potential biomarkers in the YH-GC group, and metabolic pathways were then constructed. YH disturbed the pathways of glycerophospholipid metabolism, primary bile acid biosynthesis, and sphingolipid metabolism, while YH-GC combination induced disruptions in phenylalanine, tyrosine and tryptophan biosynthesis, tyrosine metabolism, and glycerophospholipid metabolism. Conclusion: The toxicities of YH and YH-GC combination above the Chinese Pharmacopoeia dose were obvious but different. Metabonomics combined with biochemical and histopathological methods can be applied to elucidate the toxicity mechanism of the YH-GC combination that caused liver, kidney and reproductive injuries in rats. Graphical abstract: